Is financial constraint an impediment to firm's high growth? - Aykut Şengül; Sermet Pekin; Ufuk Alkan (Borsa İstanbul Review, 2025)
This paper investigates how financial constraints impede firms' ability to achieve high growth. Using a comprehensive panel dataset of Turkish firms from 2012 to 2021, we analyze the relationship between short-term debt intensity - our proxy for financial constraints - and firms' likelihood of becoming high-growth enterprises, measured by turnover and employment expansion. Employing rigorous econometric techniques, including fixed-effects logit, instrumental variable estimations, and dynamic panel GMM, we find that higher short-term debt significantly reduces the probability of high growth. Our findings highlight the crucial role of external financial frictions in shaping firm growth dynamics, particularly in emerging markets characterized by underdeveloped long-term credit markets. These results offer new insights into the broader literature on high-growth firms by integrating external financing constraints into the growth narrative.
Keywords: C40; C55; C60; C81; L25; 330; Financing constraints; Firm dynamics; High-growth firms; SMEs